MULTI-OBJECTIVE OPTIMIZATION AIMING THE SUSTAINABLE DESIGN OF FRP COMPOSITE STRUCTURES - Carlos Alberto Conceição António (2018)
The optimal design of hybrid composite stiffened structures addressing the sizing, topology and sustainable material selection in a multi-objective optimization framework is proposed. Minimum weight (cost), minimum strain energy (stiffness) and maximum sensitivity to sustainable factors (minimum variability of energy) are the objectives of the proposed structural robust design approach. The model performs the trade-off between the performance targets against sustainability, depending on given stress, displacement and buckling constraints imposed on composite structures. The design variables are ply angles and ply thicknesses of shell laminates, the cross section dimensions of stiffeners and the variables related to material selection for sustainability and distribution on structure.